First, rewrite this expression as:
#(4 * 5)/2((a^2 * a^2)/a^3)((b * b)/(b^2 * b^4)) =>#
#20/2((a^2 * a^2)/a^3)((b * b)/(b^2 * b^4)) =>#
#10((a^2 * a^2)/a^3)((b * b)/(b^2 * b^4))#
Next, use this rule of exponents to rewrite the numerator for the #b# terms:
#a = a^color(red)(1)#
#10((a^2 * a^2)/a^3)((b^color(red)(1) * b^color(red)(1))/(b^2 * b^4))#
Then, use this rule of exponents to multiply the numerators for both the #a# and #b# terms and the denominator for the #b# term:
#x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))#
#10((a^color(red)(2) * a^color(blue)(2))/a^3)((b^color(red)(1) * b^color(blue)(1))/(b^color(red)(2) * b^color(blue)(4))) =>#
#10(a^(color(red)(2)+color(blue)(2))/a^3)(b^(color(red)(1)+color(blue)(1))/b^(color(red)(2)+color(blue)(4))) =>#
#10(a^4/a^3)(b^2/b^6)#
Next, use these rules of exponents to complete the simplification of the #a# term:
#x^color(red)(a)/x^color(blue)(b) = x^(color(red)(a)-color(blue)(b))# and #a^color(red)(1) = a#
#10(a^color(red)(4)/a^color(blue)(3))(b^2/b^6) =>#
#10a^(color(red)(4)-color(blue)(3))(b^2/b^6) =>#
#10a^color(red)(1)(b^2/b^6) =>#
#10a(b^2/b^6)#
Now, use this rule of exponents to complete the simplification for the #b# term:
#x^color(red)(a)/x^color(blue)(b) = 1/x^(color(blue)(b)-color(red)(a))#
#10a(b^color(red)(2)/b^color(blue)(6)) =>#
#10a(1/b^(color(blue)(6)-color(red)(2))) =>#
#10a(1/b^4) =>#
#(10a)/b^4#